2021
DOI: 10.4103/idoj.idoj_282_21
|View full text |Cite
|
Sign up to set email alerts
|

Platelet-rich fibrin, preparation and use in dermatology

Abstract: The goal of these recommendations is to provide a framework to practitioners for implementing useful, evidence-based recommendations for the preparation of platelet-rich fibrin (PRF) and its use in various dermatological indications. The Indian Association of Dermatologists, Venereologists and Leprologists (IADVL) assigned the task of preparing these recommendations to its taskforce on platelet-rich plasma. A comprehensive literature search was done in the English language on the PRF across multiple databases.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 42 publications
(57 reference statements)
0
11
0
Order By: Relevance
“…Recently, PRF has been introduced in the treatment of different diseases to overcome the limitations of PRP. In PRF there is no need of anticoagulant, in addition to the gradual and extended release of growth factors by platelets and leukocytes entrapped within the fibrin matrix in PRF [ 6 , 13 , 14 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, PRF has been introduced in the treatment of different diseases to overcome the limitations of PRP. In PRF there is no need of anticoagulant, in addition to the gradual and extended release of growth factors by platelets and leukocytes entrapped within the fibrin matrix in PRF [ 6 , 13 , 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…The autologous growth factors in PRP and PRF work in synergism with growth factors created by skin needling to improve the collagen remodeling and wound healing. It was found that the growth factors in PRP were released almost totally in first 15 min of injection, requiring more number of sessions at frequent intervals [ 14 , 16 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…In tendon regeneration, PRF biomaterials are paving the way for new therapeutic strategies that may overcome the limitations of current tendon reconstruction surgical [19][20][21]. PRF biomaterials have been used in various dermatological treatments for various skin disorders [22,23].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies mention the use of anticoagulants and rapid release of growth factors as potential/theoretical drawbacks of PRP [6][7][8]; however, disadvantages of these properties have not been evaluated directly in terms of efcacy or safety. Such potential concerns led to the development of second-generation platelet concentrates where blood was drawn without anticoagulant and centrifuged immediately [9].…”
Section: Introductionmentioning
confidence: 99%